Diamagnetic Levitation of Bubbles and Droplets - Hunter-Brown, George (2023)
This thesis describes the use of diamagnetic levitation to study fluids in a zero-gravity environment, particularly focusing on bubbles and droplets. We use a strong nonhomogeneous magnetic field (maximum field strength 18.5~T) generated by a superconducting solenoid magnet to repel/attract materials at a molecular level allowing for a net zero body force to be experienced by bubbles/droplets. A new technique that allows for the suspension of spherical gas bubbles in liquids at room temperature is presented. The development of this technique allowed for several novel experiments to be carried out.